Role of Lewis Acids of MIL-101(Cr) in the Upgrading of Ethanol to n-Butanol - Zhou, Jian; Tong, Yuqin; He, Yaohui; Tu, Pengxiang; Xue, Bing; Cheng, Yunhui; Cen, Jie; Zheng, Yifan; Ni, Jun; Li, Xiaonian (Frontiers in Chemical Engineering, 2020)
The upgrading of bio-ethanol to n-butanol has recently been a focus of considerable attention due to the advantages of n-butanol over bio-ethanol as a sustainable fuel. The efficiency of this reaction is highly dependent on the development of catalysts, in which the understanding of how catalysts perform is essential. However, traditional catalysts are normally composed of several kinds of active sites that work together in a synergistic way in reactions, which makes it difficult to identify the role that individual active sties play. Herein, we synthesized three MIL-101 (Cr) with different Lewis acidity but without any basic sites. A linear relationship of Lewis acidity with their dehydration and condensation abilities suggests that there is a competition between the ethanol dehydration to diethyl ether and acetaldehyde condensation on Lewis acids. Upon the introduction of Pd, the Lewis acidity also dominates the particle size of Pd and then the dehydrogenation and hydrogenating abilities of catalysts.